Sistem Informasi Manajemen data Aktivasi Meter dan Transaksi Energi pada PLN Unit Layanan Pelanggan Banjarbaru Berbasis WEB - Habibi, Ahmad; Prastyaningsih, Yunita; Sayyidati, Rabini; Sabella, Billy; Santoso (Telcomatics, 2025)
PLN Customer Service Unit (ULP) Banjarbaru, through its Energy Transaction Division (TE), is responsible for processing meter activation data and energy transaction calculations. Currently, the process of combining siaga reports and DILL data is performed manually, which is time-consuming and prone to calculation inaccuracies for additional charges. To address this issue, this study aims to design and develop a Web-Based Meter Activation Data Management and Energy Transaction Information System to enhance efficiency, accuracy, and speed in data management. The system development method used is the Waterfall model, consisting of system analysis, design, coding, and testing stages using the blackbox testing method. The system is designed using an Entity Relationship Diagram (ERD), Data Flow Diagram (DFD), and Flowchart, and is built with PHP, HTML, MySQL database, and the CodeIgniter 4 (CI4) framework. Testing results show that the system performs as expected, assisting staff in recording, managing, and reporting meter activation data and energy transaction calculations more efficiently and accurately.